Report of the Task Force to Study the problems of Childhood Malnutrition - Planning Commission (Planning Commission Government of India, 2009)
The Task Force Report on Childhood Malnutrition in India (2009) highlights the persistent and widespread undernutrition among children, emphasizing its severe implications on physical and cognitive development, productivity, and intergenerational poverty. According to the NFHS-3 data, 46% of children under three are underweight, with stunting at 38.4% and wasting at 19%, alongside a rising prevalence of anemia. The report identifies immediate causes, such as inadequate dietary intake and health issues; underlying causes including poverty, gender disparities, and limited healthcare access; and structural factors affecting nutrition outcomes. Despite initiatives like the Integrated Child Development Services (ICDS), malnutrition remains prevalent due to implementation gaps, inadequate training, and funding shortfalls. The Task Force recommends a multi-faceted approach encompassing early childhood nutrition, promotion of exclusive breastfeeding, improved antenatal care, nutritional support for adolescent girls, integration with employment schemes to enhance food security, and robust community engagement through mothers’ groups and Self-Help Groups (SHGs). Further, it emphasizes strengthening capacity among Anganwadi workers and health functionaries, establishing reliable nutritional monitoring mechanisms, universalizing services, and integrating nutrition programs with broader health and sanitation initiatives. The report concludes that a comprehensive, multi-sectoral strategy is essential to effectively reduce childhood malnutrition, improve health outcomes, and foster long-term socio-economic development in India.
Planning Commission Government of India New Delhi, August 2009
Keywords: Childhood Malnutrition; Integrated Child Development Services; Infant Nutrition; Stunting; Wasting; Anemia; Maternal Health; Community Participation; Nutritional Monitoring; Vulnerable Populations; Policy Recommendations; Capacity Building